PERANAN PERADILAN AGAMA DALAM PERTUMBUHAN DAN DINAMIKA HUKUM KEWARISAN DI INDONESIA - Hamzah Hamzah (IAIN BONE, 2020)
AbstractThis study examines the role of religious courts in the construction of Islamic inheritance law. Its urgency is to open the dimensions of birth and the growth of inheritance law in the development period of religious courts. In addition, it opens up concrete reasons for the existence of the inheritance law bill that has yet to reach a climax. The methodology in this study is a narrative literature study, with a historical approach by observing juridical aspects in the growth of inheritance law.The findings in this study show that Islamic law existed since the era of the sultanate and was used as an applied law in society, including inheritance law that has been embedded in Islamic law. The authority of the religious judiciary in the field of inheritance became disoriented when the colonialists entered the colonies by applying the receptiveness theory as outlined in the form of the Staatsblad. The climax of the authority of the religious courts is the unification of the judiciary (one roof system) and its independence as the executor of judicial power. The challenge for religious courts in the field of inheritance is the unavailability of material law and the inheritance law bill which creates uncertainty.Keywords: Dynamics; Inheritance law; Religious Courts.